2014
DOI: 10.1515/dmdi-2014-0009
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacogenetics of carboxylesterases: CES1 and CES2 genetic variants and their clinical effect

Abstract: Human carboxylesterase 1 (CES1) and carboxylesterase 2 (CES2) are serine esterases responsible for the hydrolysis of ester and amide bonds present in a number of pharmaceutical products. Several common genetic variants of the CES1 and CES2 genes have been shown to influence drug metabolism and clinical outcomes. Polymorphisms of the CES1 gene have been reported to affect the metabolism of dabigatran etexilate, methylphenidate, oseltamivir, imidapril, and clopidogrel, whereas variants of the CES2 gene have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 51 publications
0
55
0
1
Order By: Relevance
“…The coregulation mechanisms of CES gene expression is still unknown. However, both genes are located in close proximity to one another on chromosome 16 (CES1 on Ch16q12.2 and CES2 at Ch16q22.1) (Langmann et al, 1997;Merali et al, 2014), which might explain the coregulation of the expression of the two CES proteins. Knowledge about the coregulated expression of DMEs is important for PBPK modeling (Achour et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coregulation mechanisms of CES gene expression is still unknown. However, both genes are located in close proximity to one another on chromosome 16 (CES1 on Ch16q12.2 and CES2 at Ch16q22.1) (Langmann et al, 1997;Merali et al, 2014), which might explain the coregulation of the expression of the two CES proteins. Knowledge about the coregulated expression of DMEs is important for PBPK modeling (Achour et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Cocaine (Pindel et al, 1997), heroin (Kamendulis et al, 1996), clopidogrel (Tang et al, 2006), aspirin (Tang et al, 2006), methylphenidate (Merali et al, 2014), enalapril/ramipril (Thomsen et al, 2014), oseltamivir , and irinotecan (Haaz et al, 1997) are some examples of drugs and prodrugs that undergo phase I metabolism by CESs, most of which are prescribed to children. In this study, hepatic CES1 and CES2 protein abundance in different pediatric age groups was determined and compared with the observed protein abundance in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Six CES1 single-nucleotide polymorphisms have been identified that in vitro exhibit various degrees of decreased activity or increased promoter activity or in vivo are associated with altered drug disposition. Three CES2 single-nucleotide polymorphisms have been associated with decreased activity both in vitro and in vivo (reviewed in Merali et al, 2014). Whether any of these genetic variants function through altered protein levels versus changes in enzyme activity is unknown, however.…”
Section: Discussionmentioning
confidence: 99%
“…The transport pathway of irinotecan is shown in Figure 1. In addition to UGT1A1 polymorphism, polymorphisms of carboxylesterase ( CES ) and ATP-binding cassette ( ABC ) genes have been reported to affect the metabolism of irinotecan 8,9. In this review, the impact of UGT1A1 genotypes on irinotecan treatment will be discussed.…”
Section: Introductionmentioning
confidence: 99%